Remittances, Poverty Reduction and Inclusive Growth in the Resource-Poor Former Soviet Union Countries - Gurbanov, Sarvar; Mammadrzayev, Vusal; Isgandar, Hasan (Springer Nature Singapore Pte Ltd., 2021)
This study researches the impact of international remittances on poverty reduction in six former Soviet Union countries. The countries where personal international remittances are equal to more than 5% of GDP and rents from natural resources are below 10% of GDP are selected as the units of measurement. This study uses a fixed effect model with robust standard errors to reveal any types of causality. According to the regression results, a 10% increase in remittance inflow reduces headcount ratio, poverty gap, and poverty severity at $1.90 per day poverty line by 4.8, 5.9 and 6.4%, respectively. In addition, the same level of increase in remittances reduces poverty headcount ratio by 3.3% and poverty gap by 3.7% at the poverty line of $3.20 per day. Additionally, pooled OLS regression results reveal that remittance inflow has a negative impact on poverty level in the above-mentioned six resource-poor countries.
Poverty Reduction for Inclusive Sustainable Growth in Developing Asia
Keywords: Migration.; Remittances.; Poverty.; Resource-poor countries.